A CLINICAL STUDY ON MANAGEMENT OF POST-OPERATIVE PAIN AND QUALITY OF LIFE OF OSTEOARTHRITIS PATIENTS AFTER TOTAL KNEE ARTHROPLASTY - T, TAMILSELVAN; H, Kalaivani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study is to assess the effect of pregabalin in the management of post-operative pain and the quality of life (QOL) of osteoarthritis (OA) patients after total knee arthroplasty. Methods: This prospective observational study was conducted in the Department of Orthopedics. A total of 96 patients were divided into two groups. Group A consists of 50 patients with the treatment of nonsteroidal anti-inflammatory drugs (NSAIDs) and Group B consists of 46 patients with the treatment of pregabalin with NSAIDs. The study subjects were followed once in 60 days for 6 months, and they were asked to answer the visual analog scale (VAS) and knee injury and OA outcome score (KOOS) questionnaire. The effect of the treatment was assessed by comparing the baseline score with follow-up score. Results: Our study result showed that the pain score of Group B in VAS at 2nd follow-up was 2.56Â±0.34 and KOOS pain score was 92.73Â±3.45 (p<0.01). The QOL score was improved significantly to 81.56Â±5.29 (p<0.01) as compared to Group A. Conclusion: The study concluded that pregabalin with NSAIDs group patients showed a better improvement in pain, symptoms, and QOL within short duration as compared to NSAIDs alone used group.